Forest structure and climate mediate drought-induced tree mortality in forests of the Sierra Nevada, USA - Restaino, Christina; Young, Derek J N; Estes, Becky; Gross, Shana; Wuenschel, Amarina; Meyer, Marc; Safford, Hugh (Ecological applications, 2019)
Extreme drought stress and associated bark beetle population growth contributed to an extensive tree mortality event in California, USA, resulting in more than 129 million trees dying between 2012 and 2016. Although drought is an important driver of this mortality event, past and ongoing fire suppression and the consequent densification of forests may have contributed. In some areas, land management agencies have worked to reduce stand density through mechanical treatments and prescribed fire to restore forests to less dense, more open conditions that are presumably more resilient to disturbance and changing climate. Here, we evaluate if stand structural conditions associated with treated (e.g., thinned and prescribed burned) forests in the Sierra Nevada of California conferred more resistance to the bark beetle epidemic and drought event of 2012-2016. We found that, compared to untreated units, treated units had lower stand densities, larger average tree diameters, and greater dominance of pines (Pinus), the historically dominant trees. For all tree species studied, mortality was substantially greater in climatically drier areas (i.e., lower elevations and latitudes). Both pine species studied (ponderosa pine [Pinus ponderosa] and sugar pine [Pinus lambertiana]) had greater mortality in areas where their diameters were larger, suggesting a size preference for their insect mortality agents. For ponderosa pine, the tree species experiencing greatest mortality, individual-tree mortality probability (for a given tree diameter) was significantly lower in treated stands. Ponderosa pine mortality was also positively related to density of medium- to large-sized conspecific trees, especially in areas with lower precipitation, suggesting that abundance of nearby host trees for insect mortality agents was an important determinant of pine mortality. Mortality of incense cedar (Calocedrus decurrens) and white fir (Abies concolor) was positively associated with basal area, suggesting sensitivity to competition during drought, but overall mortality was lower, likely because the most prevalent and effective mortality agents (the bark beetles Dendroctonus brevicomis and D. ponderosae) are associated specifically with pine species within our study region. Our findings suggest that forest thinning treatments are effective in reducing drought-related tree mortality in forests, and they underscore the important interaction between water and forest density in mediating bark beetle-caused mortality.